Spiritual Well-Being: Scale Development and Validation - Selami Kardaş (Spiritual Psychology and Counseling)
The spiritual well-being scale was developed as a way of assessing how well adults’ lives align with their values and their understanding of ultimate meaning in personal, social, environmental, and transcendental terms. The items on the scale were selected based on existing literature and essays addressing spirituality. The scale was then shown to 17 specialists in spirituality and edited in response to their comments to produce the last version of each item. The scale, composed of 49 items, was then administered to 865 adults (498 women, 57.6%; 367 men, 42.4%). Based on the results, the item set was then resolved to a 29-item scale, and Exploratory Factor Analysis revealed three significant dimensions of spirituality, which are transcendence, harmony with nature, and anomie. Construct validity and reliability were empirically ascertained and the goodness of fit was determined for the proposed model of spiritual well-being. (KMO: 951, when eigenvalue is 2; total item explanation variance: 58.337 %). The ensemble of the model’s coefficients are x²/sd = 4.11, RMESEA = .06, SRMR = .50, NFI = .90, CFI = .92. The results show that the Spiritual Well-Being Scale has the ability to measure adults’ spiritual well-being in a valid and reliable manner.